Effect of microwave assisted hydrodistillation extraction on extracts of Ficus deltoidea - Azilah, Ajit; Mohd Nazarni, Che Isa; Ahmad Ziad, Sulaiman; Nailaa, Aishath (Elsevier Ltd, 2018)
Ficus deltoidea or ‘mas cotek’ is among the well-known traditional herbal plants in Peninsular Malaysia that drawn much attention of growers worlwide because of their bioactive compounds used in reducing the risk of cancer, diabetes and heart diseases. Vitexin and isovitexin are two remarkable compounds of flavone C-glycosides found in the leaves extracts of Ficus deltoidea and chosen as biomarkers due to their abundant phytochemical and pharmacological activities. The conventional extraction methods have been used for decades. However, in this research, extraction of vitexin and isovitexin were improved by the implementation of microwave. Microwave-assisted hydrodistillation (MAHD) extraction can enhance the extraction efficiency by disrupting the plant cell wall, facilitate the solvent penetration into plant material and allow the intracellular product release by using microwave energy to heat solvents in contact with a sample and accelerate the mass transfer of target compounds from the sample matrix. The effect of main factors which were extraction temperature, irradiation time, microwave power and plant material to water ratio were investigated to obtain a maximum vitexin and isovitexin yield. As a result, the best condition that has been determined for highest vitexin and isovitexin production were under 70oC for 120 minutes at water to raw material ratio 1:10 using 500W power. This best condition of extraction of vitexin and isovitexin was finalized based on its highest yield obtained from the microwave which were 33.40 ± 0.98 (% w/w) with 1.152-fold and 11.38 ± 0.86 (% w/w) with0.65-fold, respectively. The conventional aqueous extraction was used as a control throughout the whole processes. High performance liquid chromatography (HPLC) was used to analyse yield of vitexin and isovitexin in the extracts.